Rethinking Education from Patients' Perspectives - Harrison, Jill; Frampton, Susan; McNeal, Gloria J.; Todorova, Elena; Wahl, Carol; Kreiger, Joan (ABNF Journal, 2019)
Person-centered care (PCC) is a term used to describe an individualized approach to patient care that engages patients and families as partners in meaningful ways to create a comprehensive, collaborative, and customized plan and experience of care. Although some healthcare fields of study, such as the Quality and Safety Education for Nurses (QSEN) model, have adopted and integrated person-centered care concepts and competencies into their curricula, there remains a critical gap in higher education to systematically integrate person-centered care into the curricula and assessment of interprofessional healthcare fields of study. While the delivery of person-centered care by healthcare professionals requires education and training in PCC concepts, this training has primarily occurred on the job, without a standardized and comprehensive curriculum to systematically teach and assess PCC competencies to students in interprofessional healthcare and medical degree programs. Until recently, the educational foundations for healthcare disciplines were drawn primarily from biomedical, business, and nursing models, not from patients' points of view. In this article, we consider why teaching and evaluating PCC concepts should be the foundation of all interprofessional health education. We first review the perspectives of relevance to our argument and then advocate for a person-centered paradigm shift for interprofessional healthcare and medical education and training. Next, we argue that integrating and evaluating students' understanding and application of PCC concepts in all healthcarerelated disciplines will ensure that graduates receive the most current and relevant preparation for careers in healthcare and that this aligns with the expectations of patients as consumers.
Num Pages: 9 Place: Lisle, United States
Keywords: Curriculum; Education; Evaluation; GenderWatch; Interprofessional education; Patient; Person-centered care; Teaching method; Y; dept.hms; peer-reviewed; ⛔ No DOI found

State Physical Education Policy Changes From 2001 to 2016 - Dauenhauer, Brian; Keating, Xiaofen; Stoepker, Peter; Knipe, Robert (Journal of School Health, 2019)
ABSTRACT BACKGROUND State policies influence the quantity and quality of educational programs delivered in schools. This study examined state physical education policy changes from 2001 to 2016 by analyzing data reported in The Shape of the Nation Report . METHODS Policies related to state mandates for physical education, time/credit requirements, assessment and fitness testing requirements, adoption of state standards, and allowance of substitutions were analyzed over 5 editions of the report using repeated measures statistics. RESULTS A majority of state physical education‐related policies have not changed over the past 15 years despite calls by numerous public health agencies for enhanced physical education in schools. There was, however, a significant increase in the number of states adopting teaching standards and requiring assessment and fitness testing in physical education, mirroring a broader shift in education toward standards, assessment, and accountability. CONCLUSIONS Despite improved rigor in physical education through the adoption of standards and assessment practices, physical education continues to be marginalized in schools by a lack of curricular time and inappropriate substitution policies. Stronger policies are needed for physical education to have a substantial impact on school health.
Keywords: dept.hms; peer-reviewed

Teaching Students with Seizure Disorders - Laughlin, Michael, Nathan M. Murata (Case Studies in Adapted Physical Education, 2019)
The adapted physical educator (APE) at this high school has a tenth grader with epilepsy in his class. The student is assigned a paraprofessional to monitor and assist him. The APE plans an indoor soccer lesson, which allows for easier participation for another student in a wheelchair, as well as better monitoring for the student with epilepsy. With the lesson underway and the paraprofessional positioned nearby, the student has a seizure. Fortunately, the APE has had some training on recognizing seizures, and the paraprofessional is there to help. Wondering what would happen if they were not there when the student began having a seizure and how to explain it to the other students, the APE creates a seizure fact and protocol sheet.
Num Pages: 4
Keywords: dept.hms; peer-reviewed

Technological Applications in Physical Education - Murata, Nathan M., Michael K. Laughlin (Case Studies in Adapted Physical Education, 2019)
The physical education (PE) teacher at this high school learns how to integrate a high-tech assistive device into his class for a new student who is nonverbal and uses a walker or wheelchair. The school’s paraprofessional disagrees that the student should be permitted to use the device during PE because it could be broken. Even with ample accommodations for physical participation, the student still has difficulty communicating with her peers and becomes agitated. Upon consulting with the student’s special education teacher, the PE teacher learns about an app-based assistive technology that could be programmed so the student can prepare when and how to use the device safely throughout class. The student blossoms in PE, as well as socially, by being able to preprogram her device to communicate more closely to real time.
Num Pages: 5
Keywords: dept.hms

Effects of an adapted physical education training package on special education teacher instruction - Laughlin, Michael K.; Murata, Nathan M.; McDougall, Dennis (Behavioral Interventions, 2019)
This study investigated the impact of an adapted physical education training package on functional motor skill instruction of three special education teachers who instructed secondary students with low-incidence disabilities. The training package emphasized teachers' use of systematic prompting and specific reinforcement teaching strategies plus adapted physical education consultation. We used a multiple baseline design and collected data on the three teachers' use of systematic prompting and specific reinforcement plans during videotaped teaching trials. We also collected data on how teachers documented their instructional strategies, and we analyzed personal reflections that teachers wrote in the journals. Results indicated that with each of the three teachers, correctly implemented functional motor skill instructional performance improved after they completed the training package.
0 citations (Crossref) [2023-10-31] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/bin.1653
Keywords: dept.hms; functional motor skills; peer-reviewed; prompting; reinforcement; severe disabilities; special education

Deploying Video Analysis to Boost Instruction and Assessment in Physical Education - Laughlin, Michael K.; Hodges, Michael; Iraggi, Taylor (Journal of Physical Education, Recreation & Dance, 2019)
Physical educators are discovering the benefits of using video analysis to support their instruction and assessment. Slow-motion playback, zoom, and voice-over narration are just some of the features built into increasingly affordable mobile devices and applications that can easily be used by teachers to support student learning. Additionally, with the use of video technology, teachers are finding creative ways to provide instant motor-performance feedback which can be easily documented for assessment purposes. Yet, with any novel technology tool, internal and external challenges exist that may prevent teachers from realizing the myriad of benefits. This article provides a background on mobile video analysis tools, along with strategies to help physical educators discover ways to effectively implement this engaging technology into their curriculum.
7 citations (Crossref) [2023-10-31] _eprint: https://doi.org/10.1080/07303084.2019.1580637
Keywords: dept.hms; peer-reviewed

Sabbatical leave follow-up report Spring 2019 - Fede, Marybeth H. (2019)
Keywords: dept.hms; faculty_collection; sabbatical_report

Social determinants of health: the how, who, and where screenings are occurring; a systematic review. - O'Brien, Kyle H (Social work in health care, 2019)
Screening for social determinants of health allows health care teams to assess and address social factors that influence one's health, mental health, and access to care. These social factors include poverty, health literacy, social support, exposure to trauma, food insecurity, and housing instability. The objective of this study was to examine what screening tools for social determinants of health are being used, in what contexts, and with what populations. Findings suggest that health literacy is the most commonly screened for, followed by trauma history, social support, food insecurity and housing across diverse contexts and populations. Results from this study can be used to inform providers of available screening tools and resources that can be readily utilized in practice.
32 citations (Crossref) [2023-10-31] Place: United States O'Brien, Kyle H. School of Health and Human Services, Department of Social Work, Southern Connecticut State University, New Haven, CT, USA. O'Brien, Kyle H. Department of Health and Movement Sciences, Southern Connecticut State University, New Haven, CT, USA.
Keywords: *Food Supply/sn [Statistics & Numerical Data]; *Health Literacy/sn [Statistics & Numerical Data]; *Health Services Accessibility/sn [Statistics & Numerical Data]; *Health Status Indicators; *Housing/sn [Statistics & Numerical Data]; *Poverty/sn [Statistics & Numerical Data]; *Social Determinants of Health/sn [Statistics & Numerical Data]; Humans; dept.hms; peer-reviewed

Validity and reliability of the lode excalibur sport cycle ergometer for the wingate anaerobic test - Lunn, William R.; Axtell, Robert S. (The Journal of Strength & Conditioning Research, 2019)
Lunn, WR and Axtell, RS. Validity and reliability of the Lode Excalibur Sport cycle ergometer for the Wingate Anaerobic Test. J Strength Cond Res XX(X): 000–000, 2019—Although multiple testing devices advertise Wingate Anaerobic Test (WAnT), capability, reliability, and validity data are sparse. The purpose was to determine whether the Lode Excalibur Sport cycle ergometer is a reliable and valid instrument to conduct the 30-second WAnT when compared with the Monark 894e Peak Bike ergometer. Recreationally active men (n = 49; 20.6 ± 2.5 years; 1.75 ± 0.07 m; and 79.1 ± 9.8 kg) completed four 30-second WAnTs: 2 each on the Lode and the Monark ergometers for peak power (PP), mean power (MP), minimum power (MinP), fatigue index (FI), and peak cadence (vmax) measurement. Interday and interunit correlation, multivariate analysis of variance, regression, and Bland-Altman analysis determined reliability and validity. Cohen's d was used to determine effect size. Relative reliability (intraclass correlation coefficient) with 95% confidence interval for Monark and Lode was very high for PP, MP, MinP, and vmax and high for FI (r > 0.83; coefficient of variation ≤ 27.0%; p < 0.01). Interunit correlation was strong for PP, MP, MinP, and vmax (r > 0.75; p < 0.001) and moderate for FI (p = 0.001). Lode PP and FI values were significantly less (p < 0.001; d > 1.18) and MinP, MP, and vmax significantly greater (p ≤ 0.001; d > 0.51) than Monark. Proportional bias was demonstrated for all variables (p < 0.04; d > 2.68) except vmax. The Lode ergometer reliably provides WAnT outcomes and correlates well to the Monark ergometer. However, differences in power values and proportional bias between differently braked instruments prevent use of the Lode ergometer for comparison of WAnT data with normative data generated by the Monark ergometer.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lunnValidityReliabilityLode2019
Keywords: dept.hms; peer-reviewed

Feasibility and safety of a group physical activity program for youth with type 1 diabetes - Ash, Garrett I.; Joiner, Kevin L.; Savoye, Mary; Baker, Julien S.; Gerosa, James; Kleck, Emma; Patel, Neha S.; Sadler, Lois S.; Stults-Kolehmainen, Matthew; Weinzimer, Stuart A.; Grey, Margaret (Pediatric Diabetes, 2019)
Background/ObjectiveMany adolescents with type 1 diabetes do not achieve 60 minutes of daily moderate-to-vigorous intensity physical activity (MVPA). Recognizing the importance of peer influence during adolescence, we evaluated the feasibility and safety of a group MVPA intervention for this population. MethodsEighteen adolescents with type 1 diabetes (age 14.12 .3 years, female 67%, black or Latino 67%, median body mass index 92%ile, A1c 79.925.1 mmol/mol, 9.5 +/- 2.3%). Intervention sessions (35minutes MVPA and 45minutes discussion) occurred 1x/week for 12weeks. Feasibility and safety metrics were enrollment, completion of intervention and assessments, cost, and hypoglycemia rates. Participants completed MVPA (accelerometry), and exploratory nutritional, psychosocial, clinical, and fitness variable assessments at baseline, 3 months, and 7 months. Hedges' effect sizes were calculated. ResultsEnrollment was 16%, and intervention completion was 56%. Assessment completion at 7 months was 67% for MVPA, nutrition, and fitness, 83% for psychosocial assessments, and 94% for clinical assessments. Cost was $1241 per completing participant. One episode of mild hypoglycemia occurred during the sessions (0.6%). Self-reported daily fruit/vegetable servings (d=-0.72) and diabetes self-management behaviors decreased over time (d=-0.40). In the 10 completers, endurance run score improved (d=0.49) from low baseline levels, while systolic blood pressure decreased (d=-0.75) and low-density lipoprotein increased (d=0.49) but stayed within normal ranges. ConclusionsThe protocol for the group MVPA intervention was safe and had some feasibility metrics meriting further investigation. MVPA levels and glycemic control remained suboptimal, suggesting the need for more intensive interventions for this population.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/065-217-762-885-796 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Accelerometry; Adolescent; Age Factors; Article; Black person; Blood Glucose; Child; Combined Modality Therapy; Diabetes Mellitus; Type 1; Diet Records; Exercise; Exercise Therapy; Feasibility Studies; Female; Group Processes; Health Behavior; Hispanic; Humans; Male; Young Adult; accelerometry; adolescent; adult; adverse event; age; behavior; blood; body mass; child; clinical article; clinical outcome; clinical protocol; clinical trial; cost; dept.hms; diabetes mellitus; disease severity; endurance; exercise; feasibility study; female; fitness; food intake; fruit; glucose blood level; glycated hemoglobin A; group process; health behavior; health program; human; hypoglycemia; insulin dependent diabetes mellitus; kinesiotherapy; low density lipoprotein; male; medical record; metabolism; multimodality cancer therapy; nutritional assessment; patient safety; peer-reviewed; physical activity; physiology; priority journal; procedures; psychosocial care; scoring system; self care; self report; systolic blood pressure; type 1; vegetable; young adult

Stakeholders' support of CSPAP sustainability after a three-year PEP grant - Egan, Catherine A.; Karp, Grace Goc; Berei, Catherine (Research Quarterly for Exercise and Sport, 2019)
tex.address: 2-4 PARK SQUARE, MILTON PARK, ABINGDON OX14 4RN, OXON, ENGLAND tex.affiliation: Egan, Catherine A.; Karp, Grace Goc, Univ Idaho, Moscow, ID 83843 USA. Berei, Catherine, Southern Connecticut State Univ, New Haven, CT 06515 USA. tex.author-email: eganca@uidaho.edu tex.da: 2019-10-31 tex.doc-delivery-number: HT4YY tex.eissn: 2168-3824 tex.journal-iso: Res. Q. Exerc. Sport tex.number-of-cited-references: 0 tex.publisher: ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD tex.research-areas: Social Sciences - Other Topics; Psychology; Sport Sciences tex.times-cited: 0 tex.type: Meeting abstract tex.unique-id: ISI:000464570500141 tex.usage-count-last-180-days: 1 tex.usage-count-since-2013: 1 tex.web-of-science-categories: Hospitality, Leisure, Sport & Tourism; Psychology, Applied; Psychology; Sport Sciences
Keywords: dept.hms; peer-reviewed; ⛔ No DOI found

Sport specialization: A survey of collegiate and professional athletes - Misasi, Sharon P.; Morin, Gary; Swartz, Daniel Reid (Research Quarterly for Exercise and Sport, 2019)
tex.address: 2-4 PARK SQUARE, MILTON PARK, ABINGDON OX14 4RN, OXON, ENGLAND tex.affiliation: Misasi, Sharon P.; Morin, Gary; Swartz, Daniel Reid, Southern Connecticut State Univ, New Haven, CT 06515 USA. tex.author-email: misasis1@southernct.edu tex.da: 2019-10-31 tex.doc-delivery-number: HT4YY tex.eissn: 2168-3824 tex.journal-iso: Res. Q. Exerc. Sport tex.number-of-cited-references: 0 tex.publisher: ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD tex.research-areas: Social Sciences - Other Topics; Psychology; Sport Sciences tex.times-cited: 0 tex.type: Meeting abstract tex.unique-id: ISI:000464570500216 tex.usage-count-last-180-days: 0 tex.usage-count-since-2013: 1 tex.web-of-science-categories: Hospitality, Leisure, Sport & Tourism; Psychology, Applied; Psychology; Sport Sciences
Keywords: dept.hms; peer-reviewed; ⛔ No DOI found

Championing CSPAPs: studies of targeted program implementers and advocates - Webster, Collin A.; Moore, Chanta; Orendorff, Karie Lee; Taunton, Sally; Mindrila, Diana; Stewart, Gregory; Lee, Joey A.; Welk, Gregory J.; Foster, Lorraine Lanningham; Gentile, Douglas; Vazou, Spyridoula; Liechty, Laura; et al. (Research Quarterly for Exercise and Sport, 2019)
tex.eissn: 2168-3824 tex.unique-id: ISI:000464570500004
Keywords: dept.hms; peer-reviewed; ⛔ No DOI found

Effect of hospitalizations on physical activity patterns in mobility-limited older adults - Wanigatunga, Amal A.; Gill, Thomas M.; Marsh, Anthony P.; Hsu, Fang-Chi; Yaghjyan, Lusine; Woods, Adam J.; Glynn, Nancy W.; King, Abby C.; Newton, Jr., Robert L.; Fielding, Roger A.; Pahor, Marco; Manini, Todd M.; et al. (Journal of the American Geriatrics Society, 2019)
OBJECTIVES: To evaluate the effect of hospitalizations on patterns of sedentary and physical activity time in mobility-limited older adults randomized to structured physical activity or health education. DESIGN: Secondary analysis of investigator-blinded, parallel-group, randomized trial conducted at 8 U.S. centers between February 2010 and December 2013. PARTICIPANTS: Sedentary men and women aged 70 to 89 at baseline who wore a hip-fitted accelerometer 7 consecutive days at baseline and 6, 12, and 24 months after randomization (N=1,341). MEASUREMENTS: Participants were randomized to a physical activity (PA; n = 669) intervention that included aerobic, resistance, and flexibility training or to a health education (HE; n = 672) intervention that consisted of workshops on older adult health and light upper-extremity stretching. Accelerometer patterns were characterized as bouts of sedentary (¡100 counts/min; ¿= 1, ¿= 10, ¿= 30, ¿= 60 minute lengths) and activity (¿= 100 counts/min; ¿= 1, ¿= 2, ¿= 5, ¿= 10 minute lengths) time. Each participant was categorized as having 0, 1 to 3, or 4 or more cumulative hospital days before each accelerometer assessment. RESULTS: Hospitalization increased sedentary time similarly in both intervention groups (8 min/d for 1-3 cumulative hospital days and 16 min/d for ¿= 4 cumulative hospital days). Hospitalization was also associated with less physical activity time across all bouts of less than 10 minutes (¿= 1: -7 min/d for 1-3 cumulative hospital days, -16 min/d for ¿= 4 cumulative hospital days; ¿= 2: -5 min/d for 1-3 cumulative hospital days, -11 min/d for ¿= 4 cumulative hospital days; ¿= 5: -3 min/d for 1-3 cumulative hospital days, -4 min/d for ¿= 4 cumulative hospital days). There was no evidence of recovery to prehospitalization levels (time effect p ¿ .41). PA participants had less sedentary time in bouts of less than 30 minutes than HE participants (-8 to -10 min/d) and more total activity (+3 to +6 min/d), although hospital-related changes were similar between the intervention groups (interaction effect p ¿ .26). CONCLUSION: Participating in a PA intervention before hospitalization had expected benefits, but participants remained susceptible to hospitalization's detrimental effects on their daily activity levels. There was no evidence of better activity recovery after hospitalization.
15 citations (Crossref) [2023-10-31] tex.eissn: 1532-5415 tex.orcid-numbers: Buford, Thomas W/0000-0002-9541-4358 Newton, Robert/0000-0002-6863-913X Wanigatunga, Amal/0000-0002-5763-5184 Gill, Thomas/0000-0002-6450-0368 Glynn, Nancy/0000-0003-2265-0162 tex.researcherid-numbers: Buford, Thomas W/B-1111-2011 tex.unique-id: ISI:000459714900011
Keywords: accelerometer; clinical trial; dept.hms; exercise; hospital; peer-reviewed; sedentary behavior

Changes in Lower Body Muscular Performance Following a Season of NCAA Division I Men’s Lacrosse - Talpey, Scott W.; Axtell, Robert; Gardner, Elizabeth; James, Lachlan (Sports, 2019)
The tactical and technical components of training become a primary emphasis, leaving less time for targeted development of physical qualities that underpin performance during the competition phase of a training program. A deemphasis on physical preparation during the in-season training phase may make athletes more susceptible to injury and decrease performance on the field. Two weeks prior to the start and one week following the conclusion of the 16-week collegiate lacrosse season, lower body force production was assessed in eight National Collegiate Athletic Association (NCAA) Division I Men’s Lacrosse athletes. Lower body force production capabilities were determined via the performance of countermovement jumps (CMJ) and drop jumps (DJ) performed on a force plate and isokinetic strength testing of the quadriceps and hamstring muscle groups across three velocities. Isokinetic strength of the hamstrings and the hamstring to quadriceps strength ratio were maintained or increased over the course of the competition phase of training. Relative peak force obtained from the CMJ and the reactive strength index from the DJ decreased significantly over the season. The maintenance of isokinetic strength and the decrease in CMJ and DJ performance may indicate the presence of neuromuscular fatigue that accumulated over the course of the season.
5 citations (Crossref) [2023-10-31] Number: 1
Keywords: Isokinetic; Power; Reactive strength; Strength; dept.hms; isokinetic; peer-reviewed; power; reactive strength; strength

Bullying perpetration and victimization among adolescents with overweight and obesity in a nationally representative sample - Rupp, Kristie; McCoy, Stephanie M. (Childhood Obesity, 2019)
19 citations (Crossref) [2023-10-31]
Keywords: dept.hms; peer-reviewed

A case for promoting movement medicine: preventing disability in the LIFE randomized controlled trial - Fanning, Jason; Rejeski, W Jack; Chen, Shyhhuei; Nicklas, Barbara J; Walkup, Michael P; Axtell, Robert S; Fielding, Roger A; Glynn, Nancy W; King, Abby C; Manini, Todd M; Mcdermott, Mary Mcgrae; Newman, Anne B; et al. (Journals of Gerontology Series A-biological Sciences and Medical Sciences, 2019)
Background: The movement profile of older adults with compromised function is unknown, as is the relationship between these profiles and the development of major mobility disability (MMD)-a critical clinical outcome. We first describe the dimensions of movement in older adults with compromised function and then examine whether these dimensions predict the onset of MMD. Methods: Older adults at risk for MMD (N = 1,022, mean age = 78.7 years) were randomized to receive a structured physical activity intervention or health education control. We assessed MMD in 6-month intervals (average follow-up of 2.2 years until incident MMD), with activity assessed at baseline, 6-, 12- and 24-month follow-up via accelerometry. Results: A principal components analysis of 11 accelerometer-derived metrics yielded three components representing lifestyle movement (LM), extended bouts of moderate-to-vigorous physical activity (MVPA), and stationary body posture. LM accounted for the greatest proportion of variance in movement (53%). Within health education, both baseline LM (HR = 0.74; 95% CI 0.62 to 0.88) and moderate-to-vigorous physical activity (HR = 0.69; 95% CI 0.54 to 0.87) were associated with MMD, whereas only LM was associated with MMD within physical activity (HR = 0.74; 95% CI 0.61 to 0.89). There were similar nonlinear relationships present for LM in both physical activity and health education (p ¡ .04), whereby risk for MMD was lower among individuals with higher levels of LM. Conclusions: Both LM and moderate-to-vigorous physical activity should be central in treatment regimens for older adults at risk for MMD.
8 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000491242600017, lens.org/077-007-606-131-474 tex.type: [object Object]
Keywords: Acceleration; Accelerometry; Age Factors; Aged; Aged; 80 and over; Aging; Confidence Intervals; Disability; Disability Evaluation; Exercise; Female; Geriatric Assessment; Humans; Linear Models; Male; Mobility Limitation; Physical Fitness; Physical activity; Prognosis; Sedentary; Sex Factors; Single-Blind Method; Walking Speed; acceleration; age; aged; aging; clinical trial; confidence interval; controlled study; dept.hms; disability; female; fitness; geriatric assessment; human; male; multicenter study; peer-reviewed; physiology; procedures; prognosis; randomized controlled trial; sex factor; single blind procedure; statistical model; very elderly; walking difficulty; walking speed

Spontaneous baroreflex sensitivity in normotensive African-American men - Latchman, Peter L.; Gates, Gregory J.; Thiel, Robert; Axtell, Robert S.; Zhu, Weili; Morin-Viall, Ally; Yue, Tianhong; Yang, Qin; Gardner, Kenneth; Meersman, Ronald E. De (Open Journal of Molecular and Integrative Physiology, 2019)
0 citations (Crossref) [2023-10-31]
Keywords: dept.hms; peer-reviewed